The Impact of Tourist Attraction Development on Destination Attractiveness and Local Economic Development: Mediation of Tourist Satisfaction - Lauraincia Van Houten (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Tourism plays a crucial role in stimulating economic growth and empowering local communities, especially in developing countries. Among the key elements of tourism development, tourist attractions serve as primary drivers in enhancing destination attractiveness and influencing tourists’ decisions to visit or revisit. However, the increase in tourist visits alone does not guarantee sustainable economic benefits unless supported by a high level of tourist satisfaction. This study aims to explore the impact of tourist attraction development on destination attractiveness and local economic development, with tourist satisfaction acting as a mediating variable. The research employs a qualitative descriptive method through a literature review approach. Data were collected from 10 selected international and national journal articles that met credibility and relevance criteria. Thematic analysis was used to identify key patterns and relationships among the concepts of attraction development, satisfaction, and economic impact. The results show that developing attractions—whether natural, cultural, or artificial—significantly enhances the appeal of destinations. When supported by high levels of tourist satisfaction, these developments contribute strongly to increasing tourist loyalty, revisit intentions, and local spending. Tourist satisfaction acts as a vital bridge that translates attractive destinations into tangible economic benefits for local communities. The findings also stress the importance of community-based approaches and value-chain management in tourism to ensure long-term sustainability. These findings can assist tourism stakeholders in formulating strategic policies and designing experiences that not only attract tourists but also promote inclusive and sustainable local economic development.